The ACR Classification Criteria for Headache Disorders in SLE Fail to Classify Certain Prevalent Headache Types - Davey, R; Bamford, J; Emery, P (Cephalalgia, 2008)
Headache is a common symptom described by patients with systemic lupus erythematosus (SLE). It is uncertain whether both the prevalence and phenotype of headache disorders seen in patients with SLE are similar to those in the general population. The current American College of Rheumatology (ACR) classification of headache disorders includes only five categories, included ‘Intractable headache, non-specific’, which is not further defined. The International Headache Society (IHS) has produced a classification which aims to include all recognized headache disorders. We compared the performance of the IHS and ACR criteria in 61 subjects with SLE. Whereas reference to the IHS criteria enabled classification of all headache disorders seen in the cohort, use of the ACR criteria resulted in failure to classify 22% of headache disorders. We suggest that the ACR criteria require revision. Until this is done, IHS criteria should be used in all future studies of headache in SLE.